2001
DOI: 10.1103/physrevlett.86.2665
|View full text |Cite
|
Sign up to set email alerts
|

Thickness-Dependent Curie Temperatures of Ultrathin Magnetic Films: Effect of the Range of Spin-Spin Interactions

Abstract: We present a simple model of spin-spin coupling which provides insight into the nature of the rapid decrease in the Curie temperature with decreasing thin film thickness n (number of monolayers). The shift of Curie temperature t(n) = 1-T(c)(n)/T(c)(infinity) follows the usual power law t(n) approximately n(-lambda) in thin films crossing over to linear behavior t(n) approximately n in the ultrathin film thickness limit. Experimental results for ferromagnetic thin films are compared, and shown to follow curves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
197
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(221 citation statements)
references
References 23 publications
19
197
1
Order By: Relevance
“…In the case of different dopants, trends for T c as a function of film thickness were reported by using different techniques. For comparison, we mention the results of Zhang and Willis based on measurements of bulk film magnetism through the magneto-optical Kerr effect (38), which were theoretically verified by Rausch and Nolting (41) in the molecular field approximation (Weiss mean-field theory) of the Heisenberg model. Furthermore, a recent ferromagnetic resonance study of Bi 2 Se 3 :Mn has revealed a stronger ferromagnetic order in the bulk than on the surface, which was attributed to the bulk layer being more homogeneously doped than the surface layer (34), in agreement with our observation.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of different dopants, trends for T c as a function of film thickness were reported by using different techniques. For comparison, we mention the results of Zhang and Willis based on measurements of bulk film magnetism through the magneto-optical Kerr effect (38), which were theoretically verified by Rausch and Nolting (41) in the molecular field approximation (Weiss mean-field theory) of the Heisenberg model. Furthermore, a recent ferromagnetic resonance study of Bi 2 Se 3 :Mn has revealed a stronger ferromagnetic order in the bulk than on the surface, which was attributed to the bulk layer being more homogeneously doped than the surface layer (34), in agreement with our observation.…”
Section: Resultsmentioning
confidence: 99%
“…For Co and Fe, T C is much higher than Ni. The experimentally available data for the transition temperature and the corresponding reduction in T C are mainly in the linear region, as discussed in [18]. More experiments to determine ξ 0 and λ are still in need.…”
Section: Eq (3) It Indicates That T B Is Proportional To the Potentmentioning
confidence: 99%
“…In the expression, T C (∞) is the Curie temperature for the bulk and T C (d), for nanoparticles with diameter d, ξ 0 is the correlation length and λ = 1/ν with ν the critical exponent. In addition to the geometric confinement effect, T C will be further modified by the free surface effect as the particle size approaches the ultrafine limit smaller than N 0 , which is the effective range of spin-spin interaction according to the simple model proposed by R. J. Zhang et al [18]. In this region, T C varies linearly with the particle size.…”
Section: Eq (3) It Indicates That T B Is Proportional To the Potentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the Curie temperature for the I ML Fe/W(l00) system is much lower than the corresponding Curie temperature of 282K for the I ML FeCW(i 10). It is known that Curie temperature is very sensitive to the film thickness, the coordination number, the capping and substrate layer thickness, and the interatomic distance [23][24][25][26][27]. Since exchange couplingJ decays as -I/R 3 [28], in which R is the interatomic distance, the Curie temperature will be dependent upon the crystallographic orientation of the thin film as demonstrated in [27].…”
Section: Uil Results and Discussionmentioning
confidence: 99%